Evaluation of the Clinical Status of Patients with Inherited Bleeding Disorders in Diyala-Iraq - Imad Ahmed Lateef (Diyala Journal of Medicine, 2019)
Background: Inherited bleeding disorders are rare diseases that are both complicated and expensive to manage, they are classified into: coagulation factor disorders, vessel wall defect and platelet disorders.